The Effects of Air Pollution on COVID-19 Related Mortality in Northern Italy - Eric Coker; Laura Cavalli; Enrico Fabrizi; Gianni Guastella; Enrico Lippo; Maria Laura Parisi; Nicola Pontarollo; Massimiliano Rizzati; Alessandro Varacca; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2020)
Long-term exposure to ambient air pollutant concentrations is known to cause chronic lung inflammation, a condition that may promote increased severity of COVID-19 syndrome caused by the novel coronavirus (SARS-CoV-2). In this paper, we empirically investigate the ecologic association between long-term concentrations of area-level fine particulate matter (PM2.5) and excess deaths in the first quarter of 2020 in municipalities of Northern Italy. The study accounts for potentially spatial confounding factors related to urbanization that may have influenced the spreading of SARS-CoV-2 and related COVID-19 mortality. Our epidemiological analysis uses geographical information (e.g., municipalities) and negative binomial regression to assess whether both ambient PM2.5 concentration and excess mortality have a similar spatial distribution. Our analysis suggests a positive association of ambient PM2.5 concentration on excess mortality in Northern Italy related to the COVID-19 epidemic. Our estimates suggest that a one-unit increase in PM2.5 concentration (μg/m3) is associated with a 9% (95% confidence interval: 6% - 12%) increase in COVID-19 related mortality.
Keywords: Q53; I18; J11; 330; COVID-19; Mortality; Pollution; Italy; Municipalities